Prioritizing the Rights of Nature: A paradigm shift in Water Resources Governance - Dias, Reinaldo (Seven Editora, 2024)
This chapter examines the integration of Rights of Nature (RoN) into water resource governance, highlighting a paradigmatic transition from anthropocentric approaches to a more ecocentric perspective. Recognizing water bodies as subjects of inherent rights proposes a fundamental shift in environmental management, emphasizing sustainability and equity. We look at the theoretical and practical implications of adopting RoN, using case studies from the Whanganui River in New Zealand, the Atrato River in Colombia, and the Laje River in Brazil to illustrate challenges and potential benefits of this approach. Legislation that recognizes the rights of rivers as legal entities shows promise in protecting vital ecological functions and ensuring their availability for future generations. However, the effective implementation of RoN faces challenges such as conflicts with economic usages, the need for cultural change, and the development of robust legal frameworks. Successful adoption of RoN will depend on collaborative efforts between communities, policymakers, and scientists. Convergence towards a more integrative and respectful governance of natural rights is essential for the sustainability of water resources in the global context. DOI:https://doi.org/10.56238/sevened2024.007-092